The Paris Framework for Climate Change capacity building - Khan, Mizanur Rahman; Roberts, J. Timmons; Huq, Saleemul; Hoffmeister, Victoria (London ; New York : Routledge, Taylor & Francis Group, earthscan form Routledge, 2018)
The Paris Framework for Climate Change Capacity Building aims to fill a gap in the literature by unearthing the ineffective and unsustainable practices of capacity building by bilateral and multilateral agencies in developing countries in the last decade, the gaps and lacunae in those processes, and the way forward. --
Keywords: Climate change mitigation -- International cooperation; Climatic changes -- Government policy